A randomised controlled trial of a self-management programme for low vision implemented in low vision rehabilitation services. Issue 2 (February 2015) - Rees, Gwyneth; Xie, Jing; Chiang, Peggy P.; Larizza, Melanie F.; Marella, Manjula; Hassell, Jennifer B.; Keeffe, Jill E.; Lamoureux, Ecosse L.
Highlights: A trial of a low vision self-management programme (LVSMP) in low vision services. Participants randomly allocated to usual services or usual services plus LVSMP. No significant group differences were found for vision-specific quality of life. A generic LVSM programme may not adequately meet the needs of a diverse group. Implications for delivery of LVSMP in practice need to be addressed. Abstract: Objective: To investigate the effectiveness of a low vision self-management programme (LVSMP) in older adults. Methods: Participants ( n  = 153) were existing clients of a national low vision rehabilitation organisation randomly allocated to usual services ( n  = 60) or usual services plus LVSMP ( n  = 93). The LVSMP was an 8-week group programme facilitated by low vision counsellors. The primary outcome was vision-specific quality of life (QoL) measured using the Impact of Vision Impairment (IVI) questionnaire. Secondary outcomes emotional well-being, self-efficacy and adaptation to vision loss were measured using the depression, anxiety, stress scale (DASS), general self-efficacy scale (GSES), and short form adaptation to age-related vision loss scale (AVL12). Results: At one and six month follow-up assessments, no significant between-group differences were found for vision-specific QoL, emotional well-being, adaptation to vision loss or self-efficacy ( p  > 0.05). Univariate and multivariate analyses revealed no impact of the intervention on outcome measures. Conclusions: In contrast to previous work, our study found limited benefit of a LVSM programme on QoL for older adults accessing low vision services. Practice implications: When implementing self-management programmes in low vision rehabilitation settings, issues of client interest, divergence of need, programme accessibility and fidelity of intervention delivery need to be addressed.